International Seminar on Re-engineering of Higher Technical and Vocational Education : 7-10 December 1998, Shenzhen, P.R. China ; proceedings - (:unkn) unknown (My University, 1998)
The volume contains the proceedings of the International Seminar on Re-engineering of Higher Technical and Vocational Education which was held in Shenzhen in December 1998. (BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; S 1.3 Berufliche Erstausbildung; S 6.3 Technische Berufe; I 2.3.4 Asien; I 2.3.2 Nordamerika; I 2.1 Deutschland; Berufsbildungssystem; Hochschulbildung; Technische Hochschule; Berufsausbildung; Technische Berufsschule; Technischer Beruf; China; Kanada; Bundesrepublik Deutschland; Indonesien; Malaysia; Thailand; Philippinen; USA